(untitled) (Huellas, 2022)
This article presents a history of land governance since the implementation of Indian reservations, known as indian removals, during the conquest of Araucanía, Chile. By applying a relational and conflict approach to land relations, the article retrieves historical forms of land reservation and their technological developments to historicize the ways in which modern-colonial rurality has developed to the present day in the Central-Southern region of Chile. The article concludes with the analysis of the emerging technologies of spatial ordering where I argue that a new regime of disciplinary ordering is developing using the plantations themselves as a means to govern space. The result is the undermining of the role of people as “inhabitants” in the assemblage with the modern territorial state. This research is based on a qualitative and interpretative analysis of data collected during the fieldwork (August to October 2014 and November 2015 to March 2016) conducted in Araucanía, Chile.